From utterances to speech acts - Kissine, Mikhail (Cambridge University, 2013)
Includes bibliographical references and index; This book purchased for The American University through a bequest by Lee Somers, M.C.S. 1922, Ph.D. 1926, and Pauline Floyd Somers, LL.B. 1918